All is lost [videorecording (DVD)] - Chandor, J. C.; Redford, Robert
An open-water thriller about one man's battle for survival against the elements after his sailboat is destroyed at sea. Using only a sextant and nautical maps to chart his progress, he is forced to rely on ocean currents to carry him into a shipping lane in hopes of hailing a passing vessel. But with the sun unrelenting, sharks circling, and his meager supplies dwindling, the ever-resourceful sailor soon finds himself staring his mortality in the face.